Advances in the rehabilitation of intensive care unit acquired weakness: A case report on the promising use of robotics and virtual reality coupled to physiotherapy. Issue 28 (10th July 2020) - Chillura, Antonino; Bramanti, Alessia; Tartamella, Francesco; Pisano, Maria Francesca; Clemente, Elvira; Lo Scrudato, Marzia; Cacciato, Giuseppe; Portaro, Simona; Calabrò, Rocco Salvatore; Naro, Antonino
Abstract: Introduction: Traditional physiotherapy is currently the best approach to manage patients with intensive care unit acquired weakness (ICUAW). We report on a patient with ICUAW, who was provided with an intensive, in-patient regimen, that is, conventional plus robot-assisted physiotherapy. Aim of this case study was to assess the efficacy of a combined approach (conventional plus robot-assisted physiotherapy), on muscle strength, overall mobility, and disability burden in a patient with ICUAW in post-ICU intensive rehabilitation setting. Patient concerns: A 56-years-old male who was unable to stand and walk independently after hospitalization in an Intensive Care Unit. He initially was provided with daily sessions of conventional physiotherapy for 2 months, with mild results. Diagnosis: The patient was affected by ICUAW. Intervention: Given that the patient showed a relatively limited improvement after conventional physiotherapy, he was provided with daily sessions of robot-aided training for upper and lower limbs and virtual reality-aided rehabilitation for other 4 months, beyond conventional physiotherapy. Outcomes: At the discharge (6 months after the admission), the patient reached the standing station and was able to ambulate with double support. Conclusions: Our case suggests that patients with ICUAW should be intensively treated in in-patient regimen with robot-aided physiotherapy. Even though our approach deserves confirmation, the combined rehabilitation strategy may offer some advantage in maximizing functional recovery and containing disability.